Design, Development and Operation of a Novel Robotic Fish Using PVC Gel Actuators - Ruyhan; Nazia Bibi; Sara Rahman; Abdullah Al Hossain Newaz; Abdul Kadir; Nasir Uddin (Engineering Research: Perspectives on Recent Advances Vol. 5, 2025)
Bionic robot fish possess the capability to transform the way the world underutilizes underwater environments. Distinct from the other biomimetic robots using conventional motor systems, MIT Robotuna, a biomimetic robot fish that exhibited unprecedented efficiency in power consumption and operation, was pioneered in the field of bionic robotics. The study aims at developing a circular soft robot with SMA actuators, operated utilizing a newly developed control strategy encompassing PID alongside Kalman filtering in addition to visual servo. Here, a bionic robot fish structure, that can swim underwater, has been designed. The active compact body is powered by eight sets of symmetric PVC gel actuators with a caudal fin. The robot’s 200 mm-long, fish structure design incorporates a 55.52 angle to optimize the fish dynamics movement. It’s a fast and smooth operation and can swim. The robot can swim fast and quietly by using the right positions and the appropriate actuators on the PVC gel actuators. The successful deployment and implementation of such bionic robot fish display the potential of soft robotics to develop agile and versatile underwater vehicles. This design entails a unique architecture that enables the robot to move safely and unobtrusively at the same time, which makes it suitable equipment for different exploration and surveillance missions in the water with speed and silent operation as the foremost concern.